IDENTITAS AGAMA, RUANG PUBLIK DAN POST-SEKULARISME: PERSPEKTIF DISKURSUS JURGEN HABERMAS - Noor, Irfan (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2012)
The politic of identity based on religion is still a major issue of Indonesian nationality.One such issue is the validity of a religious groupâs involvement in the national publicpolicy in Indonesia.In this context, the theory of Jurgen Habermasâs discourse and itsrelation to his view of post-secularism was very relevant to discuss. For Habermas, theneutrality of the public sphere does not mean that a vacuum of religion. In the name ofdemocracy, religious positions should be placed in parallel with the formation of otherpolitical opinions and aspirations. Functional differentiation in modern society leadingto the individualization of religion does not necessarily imply loss of influence andrelevance of religion in the public sphere. Nevertheless, of course, the involvement ofreligion in the public sphere still has limits, that the religious language of particularreligion must be âtranslatedâ into the language first that being accepted by the public,which has âepistemic statusâ that can be accepted by the other residents. Such alignmentis called âpostsekularâ people, where every citizen has the right faith with the bond ofcommunication with each other.